Microbial Insights in Dentistry: Implications for Oral and Systemic Health - Manar Ibrahim Ahmed; Marwa Siddik Abdulrazzaq; Huda Muneer Hashim (Dentistry 3000, 2025)
The relationship between microbiology and dentistry is a cornerstone for understanding oral and systemic health dynamics. The oral cavity serves as a habitat for a diverse microbial ecosystem, which contributes to both health and disease. While a balanced oral microbiome is essential for homeostasis, its dysbiosis is implicated in dental diseases such as caries and periodontitis and systemic conditions including cardiovascular disease, diabetes, and adverse pregnancy outcomes. This review delves into the role of the oral microbiome in maintaining health, the challenges of antimicrobial resistance, and the advancements in microbial diagnostics and therapeutics. It also highlights the potential of emerging technologies and microbial-based therapies in advancing personalized dentistry. Emphasizing a multidisciplinary approach, this review provides a comprehensive understanding of how microbial research can revolutionize dental practices and patient outcomes.